2006
DOI: 10.1300/j010v42n03_13
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Provider Relationships, HIV, and Adherence

Abstract: This paper analyzes data collected through focus groups of patients at an outpatient AIDS clinic at a New York medical center. Seven focus groups were conducted with 42 HIV+ patients, and verbatim transcripts of focus group sessions were analyzed through a combination of ethnographic and content analysis. We examined patients' reports of interactions with and attitudes toward their providers and attempted to define what elements in the provider-patient relationship are necessary to enable patients to become mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 6 publications
1
19
1
1
Order By: Relevance
“…25 The importance of patientcentered care in engagement, retention, and adherence has been described in treatment settings. 30,31 Previous studies have shown that healthy MSM access healthcare less than the general male population. 32,33 Our study suggests that accessing PrEP may be a gateway for MSM to engage in regular HIV/STI testing, health monitoring, and other preventive services.…”
Section: Discussionmentioning
confidence: 99%
“…25 The importance of patientcentered care in engagement, retention, and adherence has been described in treatment settings. 30,31 Previous studies have shown that healthy MSM access healthcare less than the general male population. 32,33 Our study suggests that accessing PrEP may be a gateway for MSM to engage in regular HIV/STI testing, health monitoring, and other preventive services.…”
Section: Discussionmentioning
confidence: 99%
“…Effective patient-clinician relationships appear to help patients overcome these challenges and achieve positive outcomes. High-quality interactions with clinicians improve HIV medication adherence [24, 25], satisfaction with care and health-related quality of life [26]. A general measure of relationship quality, feeling known as a person, is associated with better adherence and HIV viral suppression [27].…”
Section: Introductionmentioning
confidence: 99%
“…In some ways it marks the success of individual and collective struggles by lay people (and particularly women) for greater control over our bodies and lives (Mitchinson, 1998), struggles actively supported by social work practitioners and scholars (Apollo, Golub, Wainberg, & Indyk, 2006;Runfola, Levine, & Sherman, 2006). As alternative to governance by others, autonomy (self governance) certainly seems preferable.…”
Section: Introductionmentioning
confidence: 99%